2016
DOI: 10.1111/joa.12528
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometrics reveals restrictions on the shape of the female os coxae

Abstract: The methodology for sex determination in human skeletal remains depends on the different bone morphologies presented by men and women. Due to their direct implications in reproduction, the whole pelvis, particularly the os coxae, shows different characteristics in either sex. The sacrum and the os coxae constitute the birth canal. In this research study, the os coxae shape is analyzed using geometric morphometrics, providing information on morphology, regardless of size or any other factor beyond the geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…Mallard et al (2017) found the outlet to be the most integrated part of the pelvis, suggesting higher integration for obstetric measurements. However, since integration reduces variability (Willmore et al, 2007), more highly integrated systems should show lower levels of variation, and the pelvic canal is the most variable region of the pelvis (Candelas González, Rascón Pérez, Chamero, Cambra‐Moo, & González Martín, 2017; Kurki, 2013; Kurki & Decrausaz, 2016). Given these nonintuitive results, a comparison of obstetric and locomotor integration is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Mallard et al (2017) found the outlet to be the most integrated part of the pelvis, suggesting higher integration for obstetric measurements. However, since integration reduces variability (Willmore et al, 2007), more highly integrated systems should show lower levels of variation, and the pelvic canal is the most variable region of the pelvis (Candelas González, Rascón Pérez, Chamero, Cambra‐Moo, & González Martín, 2017; Kurki, 2013; Kurki & Decrausaz, 2016). Given these nonintuitive results, a comparison of obstetric and locomotor integration is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…This result alone indicates that this method is effective and that 3-D geometric morphometrics can be used to distinguish between the sexes on smaller portions of the pelvis. Experienced forensic anthropologists using morphoscopic methods can accurately determine sex approximately 90–95% of the time, depending on the state of the bones and the experience of the user [ 1 , 3 , 15 ]. Similar studies, which collected landmarks across the entire os coxa reported similarly high results, so it is promising to see that the method can be narrowed down to a smaller portion of bone and still retain high accuracy [ 3 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Geometric morphometric analyses are also advantageous because they consist of non-destructive techniques. Metric analyses are also more objective and generally require less training and experience than visual analysis techniques [ 15 ]. Geometric morphometrics is commonly utilized in biological studies and has more recently become a more commonly utilized method of analysis in anthropological studies as well [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is based on the study of the variety of physique features of somatotypes. In modern medical anthropology and medicine, the Constitution is evaluated as a complex of individual morphofunctional features of an individual [6]. N. Pende (1922) proposed a classification by predominance functions of one or another endocrine gland.…”
Section: G Nсandelas Et Al (2017) Believe That the Constitutionmentioning
confidence: 99%